Development of Ethnoscience Based Science Learning Module and Science Literacy for Junior High School Students - Anggraini, Atika; Prassastie, Fadilla Eka; Salani, Hana Talia Novia; Fahma, Farisa Aina; Rahman, Àdnan; Dewi, Ardiana Fatma (Proceeding International Conference on Education, 2025)
This research aims to develop ethnoscience-based science learning module and science literacy for grade VIII students. This module development uses the Research and Development (R&D) model by adapting the steps of the 4D model, which includes (Define, Design, Develop, Dessimination). In this study, data were collected through observation, interviews, questionnaires, and documentation. The developed module was validated by material experts, media experts, LKPD experts, and readability experts who each provided an assessment of the relevant aspects. The results of validation by material experts, media experts, LKPD experts and readability experts showed 100% feasibility. The results of student responses showed very good results of 88.10%. Students who use this module are better able to connect scientific knowledge with the context of science which is an important indicator in the ability to think critically, analytically, and creatively. The results of this study indicate that ethnoscience and science literacy-based modules are not only effective in improving understanding of material concepts, but also strengthening higher-order thinking skills that are needed in facing the challenges of today.